Upaya Pencegahan Nyeri Punggung dan Kelainan Tulang Belakang Melalui Edukasi Posisi Duduk Ergonomis - Cahyaningrum, Gyta; Naheria, Naheria; Cahyono, Didik; Fauzi, Muhammad Sukron (Lembaga Dongan Dosen, 2025)
The habit of sitting in an inappropriate and sustainable position can cause back pain and the risk of spinal disorders. This community service aims to educate the importance of ergonomic sitting positions to prevent back pain and spinal disorders in students of SDN 004 Samarinda Ilir. This activity was carried out through socialization and simulation for 100 students, and it involved teachers in ergonomic discussions and practices. The results of the service showed an increase in students' understanding of the correct sitting position. The percentage of students who understand how to sit properly increased from 35% to 85% after socialization. In addition, the wrong sitting habits such as slouching hanging legs, and sitting with the back tilted to the side, decreased from 40% to 10%. The conclusion of this service activity is effective in increasing student awareness about the importance of ergonomics in preventing back pain and spinal disorders in students of SDN 004 Samarinda Ilir and producing real improvements in healthier sitting posture behavior.